A Caffeic Acid Derivative Potential for Anticancer Drug: Synthesis of N-(piperidinyl)caffeamide and Its Activity against P388 Leukemia Murine Cells - Firdaus Firdaus; Nunuk Hariani Soekamto; Syadza Firdausiah; Musrifah Tahar (Hasanuddin University, 2020)
Some esters and amide derivatives of p-hydroxycinnamic acid have anticancer activity. However, the amide compound is more stable to metabolic reactions compared to its ester derivative. In this research, the synthesis of a new compound, namely N-(piperidinyl)caffeamide (M5) and its anticancer activity assay, has been conducted. The compound M5 was synthesized using p-hydroxycinnamic acid and piperidine as starting materials, and the activity assay was carried out against P388 Leukemia Murine Cells by the MTT method. By these methods, the compound M5 was obtained a yellowish crystalline with a melting point of 212-214°C, and it was very active as an anticancer with an IC50 value of 0.861 μg/mL. This compound was more active than the analog compounds previously synthesized.